Sekolah Unggulan Tuntutan Pendidikan Global - Syuhud Syuhud (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2019)
The development of the world of education is very fast and competitive, the global world has contributed a lot to the direction of change in the education world, including in Indonesia. This change requires every educational institution to keep pace with the times in dynamic changes and competition, educational institutions that are able to show their superiority will be able to enter in this competition. The superior school which is the dream of all circles and groups should have clear terminology that can be understood by everyone, so that the word